COUNSELLING INTERVENTIONS FOR THE SPECIAL NEEDS STUDENTS IN SECONDARY SCHOOLS IN EKITI STATE - C. S. Ayodele; G.O. Okon; F.O. Ibimuluyi; D. R. Adebiyi (European Scientific Journal, ESJ, 2013)
The purpose of this study was to find the counselling interventions for the Special Needs Students in some Secondary Schools in Ekiti State. Three research questions and three hypotheses were formulated for the study. A self constructed instrument is titled “Counselling Interventions for the Special Needs Students” was used for the study. A sample of fifty two respondents was selected using purposive sampling technique. Data were analysed using descriptive and inferential statistics. Results showed that there is no significant difference in terms of class and age but there is difference on the basis of gender on counselling interventions for the special needs students in Ekiti State. Recommendations were made to government, corporate bodies, teachers, counsellors, parents and individual which would enable them develop in order to achieve a high level of self sufficiency and not to be at the mercy of inadequate support services.